Effects of Two Bacterial Exopolysaccharides on Microbial Community, Fermentation Characteristics and Aerobic Stability in Oat Silage - Wei Liu; Zhijun Wang; Lin Sun; Shuai Du; Gentu Ge; Yushan Jia (Microbial Biotechnology)
ABSTRACT This study investigated whether two exopolysaccharides could serve as exogenous carbon sources to enhance fermentation quality in oat silage, providing a theoretical foundation for their future application in silage. The oats were harvested at the heading stage and, following a period of wilting, were chopped into 2–3 cm lengths for the ensiling experiment. The treatments applied were as follows: (1) a control group (CK), which received only sterile water; (2) a group with added dextran (D); and (3) a group with added levan (L). The fermentation process was monitored at various intervals: 3, 7, 14, 30 and 60 days (d), respectively. Following 60 days of ensiling, the silage was subjected to a 5‐day period of aerobic exposure (AE). EPS changed the fermentation quality of silage, altered the composition of the bacterial community, and had an impact on the feature dissimilarity between sample groups. Meanwhile, EPS showed different regulatory effects on carbohydrate metabolism at different fermentation times. EPS treatment increased the lactic acid content and decreased the pH of silage. After 60 days of fermentation, the treatment also increased the relative abundance of Lactobacillus. Dextran and levan increased the relative abundance of Hafnia–Obesumbacterium and Sediminibacterium, respectively. Under the treatment of dextran, silage retained more WSC content and achieved higher aerobic stability. Upon comparing the bacterial correlation networks, it became evident that the fermentation time altered the composition of inter‐bacterial correlations. In conclusion, EPS can effectively enhance the fermentation quality of oat silage, with dextran yielding the most pronounced positive effects.